Laparoscopic management of enterohepatic migrated fish bone mimicking liver neoplasm: A case report and literature review - Chen, Jun (Medicine (Baltimore), 2019)
RATIONALE: Accidental ingestion of a foreign body is common in daily life. But the hepatic migration of perforated foreign body is rather rare. PATIENT CONCERNS: A 37-year-old man presented with a history of vague epigastric discomfort for about 2 months. DIAGNOSIS: A diagnosis of the foreign body induced hepatic inflammatory mass was made based on abdominal computed tomographic scan and upper gastrointestinal endoscopy. INTERVENTIONS: The patient underwent laparoscopic laparotomy. During the operation, inflammatory signs were seen in the lesser omentum and segment 3 of liver. B- Ultrasound guided excision of the mass (in segment 3) was performed. Dissecting the specimen revealed a fish bone measuring 1.7 cm in length. OUTCOMES: The patient recovered uneventfully and was discharged on day 5 after surgery. LESSONS: This study shows the usefulness of endoscopy for final diagnosis and treatment in foreign body ingestion. Early diagnosis and decisive treatment in time are lifesaving for patients with this potentially lethal condition.